2011
DOI: 10.1186/1471-2334-11-93
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological aspects of a hepatitis E outbreak in Bangui, Central African Republic

Abstract: BackgroundOutbreaks of hepatitis E frequently occur in tropical developing countries during the rainy season due to overflowing drains, short-circuiting of networks of clean water and use of contaminated water from wells. Hepatitis E virus (HEV) infections are usually accompanied by general symptoms of acute liver disease. This study was conducted to define the clinical and epidemiological aspects of the HEV outbreak that occurred in May 2004 in Bangui.MethodsBlood samples were collected from 411 patients aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 38 publications
(39 reference statements)
6
29
1
Order By: Relevance
“…Turkey is a country in the European Union, and socioeconomic conditions there are better than those in the community where this study was done. Goumba et al [16] found a prevalence rate of 78% during an epidemic of HEV infection in Bangui, Central African Republic. The prevalence of hepatitis E in an epidemic period would obviously be higher than in a non-epidemic period.…”
Section: Discussionmentioning
confidence: 99%
“…Turkey is a country in the European Union, and socioeconomic conditions there are better than those in the community where this study was done. Goumba et al [16] found a prevalence rate of 78% during an epidemic of HEV infection in Bangui, Central African Republic. The prevalence of hepatitis E in an epidemic period would obviously be higher than in a non-epidemic period.…”
Section: Discussionmentioning
confidence: 99%
“…HEV outbreaks have been reported from 14 countries: Egypt, 66 Kenya, 67,68 Sudan and South Sudan, [69][70][71][72][73][74][75][76] Central African Republic (CAR), [77][78][79] Uganda, [80][81][82][83][84] Chad, 73,76,[85][86][87][88][89] Republic of Djibouti, 90 Algeria, 85,86,89,91 Namibia, 92,93 Morocco, 94,95 Somalia, 96,97 Ethiopia, 98 South Africa, 99 and Cameroon 100 (Fig. 2 and Table S2).…”
Section: Africamentioning
confidence: 99%
“…50 In addition to this outbreak, laboratory-confirmed outbreaks have occurred in Chad (1983Chad ( -1984 involving French soldiers, 51 and among natives of Mostaganem, Algeria, during 1979-1980. 52 Since 2000, outbreaks have occurred in Central African Republic, 53,54 Chad, 55 Democratic Republic of Congo, 56 Sudan, 57 and Uganda. 58 Several of these outbreaks have occurred in refugee camps in Uganda 59 and Darfur, Sudan.…”
Section: Africamentioning
confidence: 99%